Melampaui Logika Konvensional: Pendekatan Paradoksal untuk Menemukan Passion di Era Ketidakpastian - Dewi, Nadya Sucia; Asbari, Masduki; Dwitarahma, Martya (AGUSPATI RESEARCH INSTITUTA, 2025)
The YouTube video titled “Paradoxical Ways to Find Passion” presented by Gita Wirjawan as a guest speaker is part of a reflective discussion series that explores non-conventional approaches to finding passion amidst the complexity of modern life. In this video, Gita Wirjawan discusses the importance of minimizing blind spots in areas of ignorance or limited personal insight as a strategy to paradoxically find passion. One of the main points raised is the importance of challenging oneself by doing things that are contrary to one's habits or main expertise. This approach aims to broaden perspectives and minimize blind spots, so that individuals can find passion through unexpected and cross-disciplinary experiences. Thus, Gita Wirjawan emphasizes that passion is not always found through the exploration of familiar interests, but rather through the courage to step out of the comfort zone and explore new, previously unfamiliar fields. This paradoxical approach encourages individuals to open themselves up to new experiences as a way to find authentic and meaningful passions.